Fullerol Nanocatalysis and Trimodal Surface Plasmon Resonance for the Determination of Isocarbophos - Huixiang Ouyang; Huixiang Ouyang; Aihui Liang; Zhiliang Jiang (Frontiers in Chemistry, 2020)
Fullerol (C60OH) has been shown to catalyze the trisodium citrate (TSC)–silver nitrate reaction to generate Ag nanoparticles (AgNPs). These AgNPs exhibit significant nanoplasmic surface-enhanced Raman scattering (SERS), resonance Rayleigh scattering (RRS), and absorption (Abs). When an aptamer (Apt) adsorbs on the C60OH surface, catalysis is inhibited, and the intensities of SERS, RRS, and Abs decrease. In the presence of isocarbophos (IPS), Apt forms a stable complex (Apt-IPS) and releases C60OH. As a result, SERS, RRS, and Abs intensities increase with increasing IPS concentration. Accordingly, a new SERS, RRS, and Abs trimodal method using Apt-labeled fullerol was established for the determination of IPS. Of the three spectral methods, SERS was the most sensitive, while the Abs method was the most cost-effective.